Implementing the National Heart, Lung, and Blood Institute's Strategic Vision in the Division of Cardiovascular Sciences. Issue 4 (15th February 2019) - Goff, David C.; Buxton, Denis B.; Pearson, Gail D.; Wei, Gina S.; Gosselin, Teri E.; Addou, Ebyan A.; Stoney, Catherine M.; Desvigne-Nickens, Patrice; Srinivas, Pothur R.; Galis, Zorina S.; Pratt, Charlotte; Kit, Brian K.; et al.
Abstract : As we commemorate the 70th anniversary of the National Heart, Lung, and Blood Institute and celebrate important milestones that have been achieved by the division of cardiovascular sciences, it is imperative that division of cardiovascular sciences and the Extramural Research community at-large continue to address critical public health challenges that persist within the area of cardiovascular diseases. The National Heart, Lung, and Blood Institute Strategic Vision, developed with extensive input from the extramural research community and published in 2016, included overarching goals and strategic objectives that serve to provide a general blueprint for sustaining the legacy of the institute by leveraging opportunities in emerging scientific areas (eg, regenerative medicine, omics technology, data science, precision medicine, and mobile health), finding new ways to address enduring challenges (eg, social determinants of health, health inequities, prevention, and health promotion), and training the next generation of heart, lung, blood, and sleep researchers. Division of cardiovascular sciences has developed a strategic vision implementation plan to provide a cardiovascular framing for the pursuit of the institutes overarching goals and strategic objectives garnered from the input of the broader National Heart, Lung, and Blood Institute community. This plan highlights 6 scientific focus areas that demonstrate a cross-cutting and multifaceted approach to addressing cardiovascular sciences, including (1) addressing social determinants of cardiovascular health and health inequities, (2) enhancing resilience, (3) promoting cardiovascular health and preventing cardiovascular diseases across the lifespan, (4) eliminating hypertension-related cardiovascular diseases, (5) reducing the burden of heart failure, and (6) preventing vascular dementia. These priorities will guide our efforts in institute-driven activities in the coming years but will not exclude development of other novel ideas or the support of investigator-initiated grant awards. The Division of Cardiovascular Sciences strategic vision implementation plan is a living document that will evolve with iterative dialogue with the National Heart, Lung, and Blood Institute community and adapt as the dynamic scientific landscape changes to seize emerging opportunities.